Minor element effect on high temperature corrosion of a low-alloyed steel: Insight into alkali- and chlorine induced corrosion by means of atom probe tomography. (November 2021) - Persdotter, A.; Boll, T.; Jonsson, T.
Abstract: High temperature corrosion remains a challenge for many high temperature applications. The corrosion resistance may be improved by the addition of minor amounts of reactive alloying elements. However, in the presence of corrosive species, such as alkali and chlorine, the corrosion rates are often highly accelerated. This study implements STEM/EDX and APT in order to shed light on a possible destructive minor element effect by investigating how the presence of minor amounts of corrosive species in the iron oxide formed on a low-alloyed steel may impair the corrosion resistance by increasing the oxide growth rate and possibly also reduce the oxide integrity. Graphical Abstract: High temperature corrosion remains a challenge for many high temperature applications. The corrosion resistance may be improved by the addition of minor amounts of reactive alloying elements. However, in the presence of corrosive species, such as alkali and chlorine, the corrosion rates are often highly accelerated. This study implements STEM/EDX and APT in order to shed light on a parallel minor element effect by investigating how the presence of minor amounts of corrosive species in the iron oxide formed on a low-alloyed steel may impair the corrosion resistance by increasing the oxide growth rate and possibly also reduce the oxide integrity. ga1 Highlights: Potassium (K) segregates to iron oxide grain boundaries (GBs) in the outward-growing scale. The segregation of K is wide, suggesting that also the surroundings of the grain boundaries are influenced by K. K-segregation in oxide GBs is suggested to be part of the mechanism for the increased oxide growth rate observed. KCl nanoclusters (≤5 nm) are observed in the outward-growing oxide, not related to the oxide grain boundaries.